Behavior of nitrogen removal in an aerobic sponge based moving bed biofilm reactor. (December 2017) - Zhang, Xinbo; Song, Zi; Guo, Wenshan; Lu, Yanmin; Qi, Li; Wen, Haitao; Ngo, Huu Hao
Highlights: The AOR and DNR of the biocarriers increased with increasing filling ratio. There was no obvious difference in AOR and DNR between R-10 and R-20. The optimum filling ratio of sponge-based MBBR was 20% with highest AGB and TN removal. The AGB amount of the carriers varied in MBBRs with different filling ratios. Abstract: This study aims to investigate the behavior of nitrogen removal in an aerobic sponge based moving bed biofilm reactor by evaluating nitrification and denitrification rates of sponge biocarriers from three aerobic moving bed biofilm reactors (MBBRs) with filling ratios of 10% (R-10), 20% (R-20) and 30% (R-30). Results showed that the highest removal efficiencies of total nitrogen in three reactors were 84.5% (R-10), 93.6% (R-20) and 95.3% (R-30). Correspondingly, simultaneous nitrification and denitrification rate (SND) was 90.9%, 97.6% and 100%, respectively. Although R-20 had the highest attached-growth biomass (AGB) per gram of sponge compared to the other two reactors, R-30 showed the maximum ammonium oxidation rate (AOR) (2.1826 ± 0.0717 mg NH4 + -N/g AGB/h) and denitrification rate (DNR) (5.0852 ± 0.0891 mg NO3 − -N/g AGB/h), followed by R-20 and R-10. These results indicated AOR, DNR and AGB were affected by the filling ratio under the same operation mode.